Inspiratory muscle training enhances jumping power and shooting performance in elite air pistol athletes - Aydin, A. S.; Yilmaz, C.; Söyler, M.; Güney, G.; Eyüboglu, E.; Karakulak, I.; Ceylan, T.; Altug, T.; Burac, D. G.; Sahinler, Y.; Çitozi, R.; Tutal, V.; et al. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background Inspiratory muscle training (IMT) has been shown to enhance respiratory efficiency, postural stabilization, and neuromuscular coordination in athletic populations. However, its effects in precision sports such as air pistol shooting remain insufficiently explored. This study investigated the impact of a 4-week IMT program on respiratory muscle strength, explosive lower-limb performance, reaction time, and shooting accuracy in competitive air pistol athletes.